1993
DOI: 10.1136/oem.50.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ethylene glycol ethers and spermatogenic disorders in man: a case-control study.

Abstract: A case-control study was conducted among first time patients at a clinic for reproductive disorders. The study group consisted of 1019 cases, defined as patients diagnosed infertile or subfertile on the basis of a spermiogram and 475 controls who were diagnosed as normally fertile by the same procedure. Possible exposure to ethylene glycol ethers was assessed by the presence of the urinary metabolites methoxyacetic acid (MAA) and ethoxyacetic acid (EAA) respectively for 2-methoxyethanol and 2-ethoxyethanol or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
3
30
1
6
Order By: Relevance
“…Studies in laboratory animals have demonstrated damage by 2-ME and 2-EE to male fertility and to the physical and aesthetic structure of offspring 24,25) . Cherry et al 26) found a significant association between intensity of exposure to solvents and clinical findings of less than 12 × 10 6 motile sperm (Odds ratios (ORs) were 2.07 (95% confidence interval (95% CI) 1.24 to 3.44) for moderate exposure and 3.83 (95% CI 1.37 to 10.65) for high exposure to solvents).…”
Section: Industrial Chemicals (Solvents)mentioning
confidence: 99%
“…Studies in laboratory animals have demonstrated damage by 2-ME and 2-EE to male fertility and to the physical and aesthetic structure of offspring 24,25) . Cherry et al 26) found a significant association between intensity of exposure to solvents and clinical findings of less than 12 × 10 6 motile sperm (Odds ratios (ORs) were 2.07 (95% confidence interval (95% CI) 1.24 to 3.44) for moderate exposure and 3.83 (95% CI 1.37 to 10.65) for high exposure to solvents).…”
Section: Industrial Chemicals (Solvents)mentioning
confidence: 99%
“…However, despite extensive exposure to the solvent, investigations regarding its effect on humans are very limited. In males exposed occupationally to EGEE, reproductive effects and anemia have previously been reported [9][10][11] . However, little is known about its health effects among women.…”
mentioning
confidence: 99%
“…Since there are differences, however, between the toxicokinetics of EGME in rodents and in humans (Groeseneken et al, 1989) and different routes of exposure in our rodent studies and in women, it will be necessary to establish the pharmacokinetic data of EGME in women in order to accurately predict exposure risks. Previous studies have addressed experimental and occupational exposures in men to determine such parameters (Groeseneken et al, 1986a,b;Veulemans et al, 1993) which may be feasible to determine in women as well.…”
Section: Discussionmentioning
confidence: 99%